Comparative evaluation of the effect of Moringa Oleifera seeds and aluminum sulfate on the removal of turbidity from the water of the Caplina river (Journal SCIENCEVOLUTION, 2024)
The present study comparatively evaluated the efficacy of Moringa oleifera seeds and aluminum sulfate in the removal of turbidity from the water of the Caplina River, Tacna, Peru. Water samples were collected at three points along the river and treated with concentrations of 20, 40, and 60 mg/L of both coagulants. The results showed that aluminum sulfate achieved a greater reduction in turbidity, reaching 97.08% efficiency at a concentration of 20 mg/L, compared to Moringa oleifera, which achieved 96.01% efficiency at the same concentration. Despite the slight superiority of aluminum sulfate in terms of efficiency, Moringa seeds offer significant environmental sustainability advantages, as they are biodegradable and do not generate toxic residues. The ANOVA statistical analysis indicated significant differences in turbidity removal among the different concentrations of Moringa (p < 0.05), highlighting the 20 mg/L concentration as the most effective. These findings suggest that Moringa oleifera is a viable and ecological alternative for water treatment in rural communities with limited resources. It is concluded that Moringa oleifera stands out as a more sustainable and safer option for drinking water treatment. Further research is recommended to evaluate the efficacy of Moringa in different contexts and to explore combinations with natural and chemical coagulants to optimize turbidity removal and minimize environmental impacts.
Keywords: Natural coagulants; Treatment effectiveness; Environmental impact; Moringa oleifera; Turbidity removal; Aluminum sulfate; Water treatment